A Stiff and Healable Polymer Based on Dynamic‐Covalent Boroxine Bonds. Issue 37 (8th July 2016) - Lai, Jian‐Cheng; Mei, Jin‐Feng; Jia, Xiao‐Yong; Li, Cheng‐Hui; You, Xiao‐Zeng; Bao, Zhenan
Abstract : A stiff and healable polymer is obtained by using the dynamic‐covalent boroxine bond to crosslink PDMS chain into 3D networks. The as‐prepared polymer is very strong and stiff, and can bear a load of more than 450 times its weight. When damaged, it can be completely healed upon heating after wetting.